2017
DOI: 10.1136/bcr-2016-218221
|View full text |Cite
|
Sign up to set email alerts
|

Pazopanib-associated posterior reversible encephalopathy syndrome with intracerebral haemorrhage

Abstract: Pazopanib is a tyrosine kinase receptor antagonist used for renal cell carcinoma and soft tissue sarcoma that inhibits tumour growth and angiogenesis. A common side effect of pazopanib is hypertension. We report a case of a 69-year-old woman with clear cell renal cell carcinoma who developed a large right occipital intracerebral haemorrhage 3 weeks after initiating pazopanib. Although this was initially suspected to be a haemorrhagic metastasis, MRI revealed bi-occipital oedema, supporting a diagnosis of poste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…For patients with PRES caused by pazopanib, it was reported that PRES occurred nine days to 2 months after the initiation of pazopanib 8–13 . In contrast, PRES occurred at day 3 after the initiation of pazopanib in our patient, which is a significant feature of this case.…”
Section: Case Descriptioncontrasting
confidence: 48%
See 2 more Smart Citations
“…For patients with PRES caused by pazopanib, it was reported that PRES occurred nine days to 2 months after the initiation of pazopanib 8–13 . In contrast, PRES occurred at day 3 after the initiation of pazopanib in our patient, which is a significant feature of this case.…”
Section: Case Descriptioncontrasting
confidence: 48%
“…Studies investigating the association between PRES and anticancer drugs have reported that PRES is more common in women 5 . As such, the activation of oestrogen was proposed to be involved in the aetiology of PRES 12 . Our patient had a history of uterine leiomyosarcoma and the oestrogen receptor is expressed in 60% of patients with the disease 19 .…”
Section: Case Descriptionmentioning
confidence: 73%
See 1 more Smart Citation